RELATIONSHIP PARENT CHILD SOCIAL INTERACTION WITHSUCCESSIN NURSERY SCHOOL DHARMA WANITA II KEDUNGADEM 2014 - Oktavia Eka Muji Rahayu; Asrina Pitayanti; Iva Milia Hani Rahmawati (STIKES Insan Cendekia Medika Jombang, 2014)
Child's social interaction was linked by the role of parents. Each world parent responsible forthe child'ssuccess in social interaction both in the lives of children with the them eas well as interacting with thecommunity at large. Too vercome this, the parents should train their children in order to interact with theirpeers and as atransmitter control functions as well asa reminder of the lessons given in schools in relation tothe interaction with peers. There fore, searchers interested in studying the role of Relationship Parent ChildSocial Interaction Withsuccessin Nursery School Dharma Wanita II Kedungadem 2014.The research design used a cross-sectional survey of analytic models of the kind of research thatemphasizesthe time measurement/observation of the independent and dependent variable data only once at atime, the population in this study were all mother and son who become students in Nursery School DharmaWanita II Kedungadem number 33 people, the samples in this study were 30 mothers and their children aredone with random sampling is random sampling. Measuring instruments used in this study was aquestionnaire.The data is processed through the stages of editing, coding, scoring, tabulating and presented in tables laterin the analysis through the Test Statisticwith Spearmans Correlation (rs) Calculate the value of Spearman'scorrelation (rs) and then compared with Table Spearman (rs table). The decision was taken from thecomparison. If rs >rs table, H0 is rejected and H1 is accepted. Means there is a significant associationbetween the two variables measured, meaning that HO is rejected and H1 is accepted.The results ofthis study concluded that there is a relationship between the role of parent to a child's successin Nursery School social in teraction Dharma Wanita II Kedungadem 2014.Key words: The role ofparents, success, socialinteraction, Children